2020
DOI: 10.1038/s41586-020-2772-0
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding and priming of the spike protein of SARS-CoV-2 for membrane fusion

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,014
3
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(1,073 citation statements)
references
References 51 publications
(91 reference statements)
41
1,014
3
15
Order By: Relevance
“…These studies suggest that the release of the S1 by receptor or antibody binding is a precondition for coronavirus fusion. Similar observations were also reported for SARS-CoV-2 [61]. Spikes in a post-fusion-like state were observed on the surface of SARS-CoV-2 with electron microscopy [43,44].…”
Section: Conformational Changes Of the Spike Proteins During Virus Entrysupporting
confidence: 85%
See 1 more Smart Citation
“…These studies suggest that the release of the S1 by receptor or antibody binding is a precondition for coronavirus fusion. Similar observations were also reported for SARS-CoV-2 [61]. Spikes in a post-fusion-like state were observed on the surface of SARS-CoV-2 with electron microscopy [43,44].…”
Section: Conformational Changes Of the Spike Proteins During Virus Entrysupporting
confidence: 85%
“…Binding of ACE2 to one SARS-CoV RBD opens up the RBD (the ACE2-bound RBD has an "up" angle of 51-111 degree compared to 52-70 degrees for the uncomplexed RBD) and induces the release of the S1 subunits from the spikes and the pre-to post-fusion conformation transition of the spike [25]. A two-RBD "up" state and a three-RBD "up" state were observed after ACE2 binding to the S of SARS-CoV-2 [61]. These states are not stable and are prone to switch to the post-fusion state.…”
Section: High-affinity Binding To the Ace2 Receptormentioning
confidence: 99%
“…Complex structural determinations have revealed the interactions between SARS-CoV-2 RBD and hACE2 at an atomic level 13-16 . Cryo-EM studies revealed that the SARS-CoV-2 S trimer, similar to that of SARS-CoV, needs to have at least one RBD in an “up” conformation to bind hACE2 17-23 . Therefore, a spike trimer with all three RBDs “down” is in a receptor-binding inactive state, and the conformational change of at least one RBD from “down” to “up” switches the spike trimer to a receptor-binding active state 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Анализ S-белков последних (по времени возникновения) штаммов из европейских стран и Китая, для которых в базе данных приводятся сведения по секвенированному геному, свидетельствуют о том, что все они содержат мутацию D614G. Ее возникновение снижает отрицательную полярность S1-субъединицы S-белка и соответственно увеличивает электростатическое взаимодействие S-белка с клеточными рецепторами коронавируса SARS-Cov-2 (ангиотензин-конвертирующим энзимом-2 и нейропилином-1, имеющими выраженную отрицательную полярность) [36], а также придает большую конформационную гибкость молекуле S-белка [37].…”
Section: проблемные статьиunclassified